2021
DOI: 10.1016/j.amjcard.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Visit-to-Visit Variability of Resting Heart Rate and the Risk of New-Onset Atrial Fibrillation in the General Population

Abstract: Resting heart rate (RHR) has been an established predictor for atrial fibrillation (AF). However, the association of visit-to-visit heart rate variability (VVHRV) with new-onset AF risk over long term remains unclear. Our study investigates the relation of VVHRV to new-onset AF in general population in the prospective study of the Kailuan cohort. A total of 46,126 individuals without arrhythmia were included. They underwent 3 health examinations from 2006 to 2010 and performed follow up. VVHRV was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In order to solve the measurement error of RHR, the coefficient of variation of heart rate (HRCV) was often calculated to represent the visit-to-visit heart rate variability (VVHRV), which became an emerging risk indicator for cardiovascular diseases. Accumulating evidence proved that VVHRV may be positively associated with risks of several cardiovascular events, such as myocardial infarction, heart failure, atrial fibrillation, and cardiovascular mortality (4)(5)(6)(7). The Systolic Blood Pressure Intervention Trial (SPRINT) trial showed that intensive blood pressure control showed significant better cardiovascular outcomes, after which the American hypertension guideline quickly reduced the blood pressure target (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the measurement error of RHR, the coefficient of variation of heart rate (HRCV) was often calculated to represent the visit-to-visit heart rate variability (VVHRV), which became an emerging risk indicator for cardiovascular diseases. Accumulating evidence proved that VVHRV may be positively associated with risks of several cardiovascular events, such as myocardial infarction, heart failure, atrial fibrillation, and cardiovascular mortality (4)(5)(6)(7). The Systolic Blood Pressure Intervention Trial (SPRINT) trial showed that intensive blood pressure control showed significant better cardiovascular outcomes, after which the American hypertension guideline quickly reduced the blood pressure target (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…One previous study demonstrated a relation of the resting heart rate and VVV-HR, which implies that increased VVV-HR may reflect the increased activity of the sympathetic system. 17 Increased VVV-HR is also an indicator of inadequate control of symptom or substrate of AF which is part of the B (Better symptom management) component of the AF Better Control (ABC) pathway, which is an important treatment target recommended in the practice guideline. 6 Moreover, previous studies have shown that patients with increased VVV-SBP, which may share similar mechanisms to VVV-HR, had a poor adherence to medications and anticoagulant control.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CAD was identified as a predictor, in line with the results of a non-stroke cohort in the Framingham Heart Study [ 33 ]. Low HR variability (measured as the variation in the beat-to-beat interval) is associated with a higher risk of AF [ 34 ], and the frequency of visit-to-visit HR variability is associated with the risk of new-onset AF in the general population [ 24 ]. However, few studies have investigated the correlation between visit-to-visit HR variability and AF in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable logistic regression analysis with backward variable selection (probability for removal > 0.05) was performed to identify predictors of pAF. According to previous studies [ 21 , 22 , 23 , 24 ], the potential candidate predictors were age, sex, eNIHSS score, hypertension, diabetes mellitus, dyslipidemia, CAD, congestive heart failure, smoking status, prior stroke or transient ischemic attack, total cholesterol level, triglyceride level, creatinine level, alanine aminotransferase level, mean systolic blood pressure, mean diastolic blood pressure, mean HR, HR-CV, and HR-SD. Stroke severity was categorized into mild (eNIHSS score ≤ 5), moderate (eNIHSS score 6–13), and severe (eNIHSS score > 13), with mild severity as the reference group.…”
Section: Methodsmentioning
confidence: 99%